PENGHIDUPAN PETANI KELAPA DI DESA APULEA KECAMATAN LOLODA UTARA KABUPATEN HALMAHERA UTARA - Yosafat Kotalaha; Gatot Sasongko (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Livelihood of Coconut Farmers in Apulea Village of North Loloda Sub-District North Halmahera District. The living conditions of the people of Apulea Village are isolated due to the limited physical capital with the main livelihoods of the people at this village come from coconut plantation farmers with copra production as a superior commodity whose processing is carried out traditionally, a strategy to survive by utilizing natural resources that supporting their needs. This study aims to describe coconut farmer household strategies in using assets to meet their household needs. This research was conducted in Apulea Village, of North Loloda Sub-District of North Halmahera District from September 2017 to November 2018. This research used qualitative method with a case study approach. The data were gathered through observation method, in-depth interview method and document study. The key informants involved in this study were selectively chosen based on their livelihood backgrounds and experiences relevant to the context of the study, which were consisted of four people. The results of this study indicated that in order to support the needs of coconut farmers in Apulea Village, four household livelihood strategies are carried out namely: “makiriwo” working group strategy of with the “leleani” philosophy, the intercropping farming strategy, the double income strategy and the patron-client strategy. Keywords: coconut farmer, livelihood strategy, livelihoods ABSTRAK Kondisi kehidupan masyarakat Desa Apulea terisolasi karena keterbatasan modal fisik, dengan komoditas unggulan yang pengerjaannya dilakukan secara tradisonal, strategi untuk bertahan hidup dengan pemanfaatan aset sumber daya alam yang mendukung untuk memenuhi kebutuhan. Penelitian ini bertujuan untuk menguraikan strategi rumah tangga petani kelapa dalam pemanfaatan aset untuk memenuhi kebutuhan hidup rumah tangga. Penelitian ini dilakukan di Desa Apulea Kecamatan Loloda Utara Kabupaten Halmahera Utara pada bulan September 2017 sampai bulan November 2018. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus. Pengambilan data penelitian menggunakan teknik wawancara mendalam, observasi, dan studi dokumen.  Informan kunci yang dilibatkan dalam penelitian ini dipilih secara selektif berdasarkan latar belakang mata pencaharian dan pengalaman yang relevan dengan konteks penelitian yang terdiri dari empat orang. Hasil penelitian ini menunjukan bahwa untuk memenuhi kebutuhan hidup petani kelapa Desa Apulea melakukan empat strategi nafkah rumah tangga, yaitu: strategi kelompok kerja makiriwo dengan filosofi leleani, strategi bercocok tanam tumpang sari, strategi nafkah ganda, dan strategi patron-klien.Kata kunci: petani kelapa, strategi penghidupan, mata pencaharian